Pembuatan Stik Daun Kelor (Moringa oleifera) sebagai Upaya Peningkatan Gizi Jajanan Lokal - Idrus, Irman; Katadi, Syaiful; Rahmat, Nurfitriyana; Salam, Muh. Ramadhan; Aprianti, Rahayu; Suriyani, Lilis; Kalsum, Ummi; Trisilia, Wiwin; Fausiyah, Afifah; Ningsih, Sri Yulia; Damayan, Elsa ti (CV. Q2 Lantera Ilmiah Institut, 2024)
Moringa oleifera leaves are known for their high nutritional content, yet their utilization remains limited. This study aimed to develop Moringa leaf-based sticks and evaluate their acceptance. An experimental method was employed, creating three stick formulations: control, 10% Moringa leaf powder (A), and 20% Moringa leaf powder (B). Proximate analysis, organoleptic tests, and community acceptance surveys were conducted. Results showed significant protein, vitamin A, and iron increases in Moringa-fortified sticks. Formulation A had the best acceptance with an average score of 4.2 out of 5 for all organoleptic parameters. Despite higher nutritional value, Formulation B was less preferred due to stronger color intensity and aroma. The survey revealed that 85% of respondents were interested in consuming Moringa sticks regularly. Education and demonstration of stick-making to the community increased interest, with 78% of respondents willing to try making them at home. In conclusion, Moringa leaf sticks have the potential to become a healthy snack alternative that can improve community nutritional intake. Further research on nutrient stability during storage and formulation optimization is needed for better acceptance..